MEWUJUDKAN KETAHANAN SOSIAL BAGI GENERASI MUDA BANGSA TERHADAP PENGARUH LITERASI MEDIA DIGITAL DI SMA 1 DAN SMA 3 KABUPATEN BOYOLALI - Indarto Kusnohadi; Mardji Tulastri; Suluh Usaha Adi; Sertar Riyan Arief Hidayatullah; Sertar Arya Prima Wiratama (PPM Sdirjianbang Akademi Militer, 2024)
The rapid development of IT advancement cannot be denied that the use of social media has become a daily necessity for most Indonesian people, including the younger generation. Likewise, students who are the young generation of the nation's successors at the level of SMA 1 and 3, which are located in Boyolali Regency, cannot be separated from the purpose of using social media. The emergence of social media platforms or applications in cyberspace such as instagram, facebook, twiter, whatsapp, blogs, youtube, line and so on, in its development has led to the mixing of information. For this lesson we use lecture and question and answer methods about software that dramatizes a documentation of events or facts so that it causes hoaxes, bullying, provocation of fakenes and hate speech among the community and ends up tearing apart the social resilience that has long been maintained. So that it requires all community leaders, religious leaders, youth leaders and managers of schools, colleges and Boarding shools to create programs as well as include them in the curriculum related to digital media literacy. The activity program resulting in a community service carried out by the Military Academy Defense Management Study Program Lecturer Team has a target; increasing the use of digital media literacy to realize social resilience for the younger generation at SMA 1 and SMA 3 Boyolali. The next goal is to increase skills to realize social resilience for young people in high school.